2008
DOI: 10.1261/rna.1024908
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intron length on exon creation ratios during the evolution of mammalian genomes

Abstract: Recent studies report that alternatively spliced exons tend to occur in longer introns, which is attributed to the length constraints for splice site pairing for the two major splicing mechanisms, intron definition versus exon definition. Using genomewide studies of EST and microarray data from human and mouse, we have analyzed the distribution of various subsets of alternatively spliced exons, based on their inclusion level and evolutionary history, versus increasing intron length. Alternative exons may be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 58 publications
7
55
1
Order By: Relevance
“…There is also no evidence for a cryptic exon, which tends to appear in longer introns. 32 So the question remains, does intron 1 of huntingtin have any particular cis-regulatory effects on the expression level of the transcript? An extremely long intron 1 increases the potential for splice factor binding sites.…”
Section: Architecture Of the Huntingtin Gene And Its Influence On Splmentioning
confidence: 99%
“…There is also no evidence for a cryptic exon, which tends to appear in longer introns. 32 So the question remains, does intron 1 of huntingtin have any particular cis-regulatory effects on the expression level of the transcript? An extremely long intron 1 increases the potential for splice factor binding sites.…”
Section: Architecture Of the Huntingtin Gene And Its Influence On Splmentioning
confidence: 99%
“…The human CASK gene encodes 17 transcripts, a significantly larger number than its orthologues in C. elegans and Drosophila, each of which produce six CASK transcripts; the surprising length of the mammalian CASK gene may thus provide more functional flexibility for mammalian CASK. Another intriguing consequence of the vast expansion of intron length in the mammalian CASK gene is the possible exonization of conserved intron sequences [26]. In fact, Dembowski et al [27] recently showed that CASK contains an inducible exon in the GuK domain that is expressed only upon neuronal stimulation.…”
Section: Gene Sizementioning
confidence: 99%
“…Long introns were also found to correlate with splice site strength, where short introns tend to flank weak splice sites and long introns tend to flank exons with strong splice sites (Fields 1990;Clark and Thanaraj 2002;Weir and Rice 2004;Dewey et al 2006). A more recent study reveals that novel alternative exons tend to appear within long introns (Roy et al 2008), suggesting that the association of alternative splicing with long introns is a consequence of the higher likelihood of new exons to originate in long introns.There is much debate over the mechanism by which the splicing machinery recognizes exons from within the vast intronic oceans. Two main models are frequently used to explain this issue: the intron definition and exon definition pathways (Robberson et al 1990;Berget 1995;Ast 2004;Ram and Ast 2007;Keren et al 2010).…”
mentioning
confidence: 93%
“…Long introns were also found to correlate with splice site strength, where short introns tend to flank weak splice sites and long introns tend to flank exons with strong splice sites (Fields 1990;Clark and Thanaraj 2002;Weir and Rice 2004;Dewey et al 2006). A more recent study reveals that novel alternative exons tend to appear within long introns (Roy et al 2008), suggesting that the association of alternative splicing with long introns is a consequence of the higher likelihood of new exons to originate in long introns.…”
mentioning
confidence: 93%